Continuous Renal Replacement Therapy Versus Intermittent Hemodialysis for Renal Prognosis in Elderly Patients With Acute Kidney Injury - Enhui Li; Linlin Zhang; Yikai He; Huipeng Ge; Rong Tang; Jinbiao Chen; Yong Zhong; Xiangning Yuan; Weiwei Zhang; Yizi Gong; Xiangcheng Xiao (International Journal of Nephrology)
Conclusions: Our study indicated that CRRT and IHD have comparable effects on renal recovery at discharge in elderly patients with AKI who require RRT. However, in comparison with IHD, CRRT was linked to a diminished likelihood of requiring RRT at 90 days.